Case of adenomyosis causing the activation of the coagulation system after a complete loss of endometrium following microwave endometrial ablation. Issue 9 (17th June 2021) - Kimura, Fuminori; Hanada, Tetsuro; Nakamura, Akiko; Amano, Tsukuru; Tsuji, Shunichiro; Kita, Nobuyuki; Murakami, Takashi
Abstract: The formation of microbleed and minute tissue necrosis inside adenomyosis after the shedding of endometrial or endometrial‐like tissue within the myometrium during menstruation is receiving attention as a new pathological condition of uterine adenomyosis. These formations might greatly affect coagulation and fibrinolysis function. However, these modulations might occur due to indirect effects of massive hemorrhage from the uterus with adenomyosis. We present a case of adenomyosis in which the patient's coagulation system was markedly activated despite the absence of menstruation due to previous microwave endometrial ablation to prevent massive uterine hemorrhage. Although no uterine bleeding was observed at all, the patient's serum levels of thrombin–antithrombin complex and soluble fibrin were abnormally elevated at the time when she complained of lower abdominal pain. As the first such case in the world, the present case is valuable for showing that the coagulation function can be modified by uterine adenomyosis.